2021
DOI: 10.1590/2318-0889202133e200068
|View full text |Cite
|
Sign up to set email alerts
|

The intellectual foundation of the elite of Brazilian researchers on knowledge organization domain

Abstract: This study aims to analyze the intellectual foundation of the literature on knowledge organization published from 1972 to 2018 by authors enrolled in the Research Productivity Fellowship from Conselho Nacional de Desenvolvimento Científico e Tecnológico, in Brazil. The corpus of analysis is composed of 166 papers indexed in Base de Dados Referencial de Artigos de Periódicos em Ciência da Informação, which is a database that gathers the scientific literature published in Information Science journals in Brazil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Subtopic 3 refers to ACA applications. Araújo and Bufrem (2021) studied the academic social structure of Brazilian researchers, Ghane et al (2019) identified the trends of information retrieval and González-Valiente (2021) of information management.…”
Section: Subtopic 3: Author Co-citation Applicationsmentioning
confidence: 99%
“…Subtopic 3 refers to ACA applications. Araújo and Bufrem (2021) studied the academic social structure of Brazilian researchers, Ghane et al (2019) identified the trends of information retrieval and González-Valiente (2021) of information management.…”
Section: Subtopic 3: Author Co-citation Applicationsmentioning
confidence: 99%